Impacto do Plano Nacional de Saneamento Básico sobre os recursos hídricos em diferentes cenários : abastecimento de água e esgotamento sanitário - Queiroz, Amanda Rojas de (2021)
Due to various conflicts of interest in water and increased demand for water, Brazil, as well as other emerging countries, face difficulties in water management. Nationally, the legal apparatus of water resources is satisfactory, however, the management and enforcement of legislation are still insufficient. An example of this reality can be seen in the application of the sanitation targets contained in the National Basic Sanitation Plan. Achieving these goals offers benefits to water resources and the health of the population. Thus, the work aims to assess whether the full implementation of the Plansab's supply and depletion goals impact on the provision of sanitation services and the quantitative water balance of the hydrographic basins. In this way, being able to direct and rank as actions in the service of sanitation to regions where the positive effects of the application of the targets are enhanced, better then the service to sanitation and the performance of the management and management of historical resources. The results indicated that the Plansab goals for urban supply have less impact on the universalization of urban and rural services. Plansab's goals for sanitary sewage reduce the load of pollutants that reach water bodies, that is, they generate more relevant impacts in the universal service provision for the sector. The surface water balance presented greater accentuation and expressiveness than the underground, indicating that it suffers a greater impact from the reduction of water pressure compared to the application of Plansab.